The effect of tax risk on audit report delay: Empirical evidence from Indonesia - Eko Suwardi; Arfah Habib Saragih (Cogent Business & Management, 2023)
Tax risk has the potential to have far-reaching economic consequences, including the effect on late audit reports. This study aims to empirically investigate the effect of tax risk on audit report lag. This study took a quantitative approach. Companies listed on the Indonesia Stock Exchange (IDX) between 2012 and 2017 were used as samples. Our final observations consist of 1,813 firm-years. We find that the tax risk has no effect on audit report lag. This finding holds up when one alternative measure of tax risk and several additional control variables are considered. The result of this study has clear implications not only for company management but also for tax authority. Company management is required to always implement good tax risk management practices because this can result in a relatively low corporate tax risk. A relatively minor tax risk will have no effect on auditors' performance in completing audit work so that companies can submit their financial reports on time. Furthermore, the tax authority benefits because the finalization of tax collection settlement is improved. Tax authority is encouraged to always maintain tax regulations that are not overly complex, complicated, or change too frequently.
Keywords: M10; M41; H26; H20; M00; 650; audit report lag; emerging country; Tax risk; tax uncertainty; timeliness of financial reporting